GENE-22. MOLECULAR ALTERATIONS AND USE OF TARGETED THERAPY IN 160 PEDIATRIC PATIENTS WITH CENTRAL NERVOUS SYSTEM (CNS) TUMORS. (23rd April 2019) - Wright, Erin; Boswell, Demetri; Sisson, Rebecca; Fuller, Christine; DeWire, Mariko; de Blank, Peter; Hummel, Trent; Fouladi, Maryam; Salloum, Ralph
Abstract: BACKGROUND: Molecular profiling is commonly performed in pediatric CNS tumors, however the clinical utilization of genomic data in pediatric neuro-oncology is not fully characterized. We describe a single institution experience adopting a personalized therapeutic approach based on tumor genetic alterations. METHODS: We retrospectively analyzed genomic data, generated using fluorescent in situ hybridization, single gene, or panel sequencing, of pediatric CNS tumors in patients diagnosed between 2010 and 2018 at Cincinnati Children's Hospital Medical Center. We aimed to identify common genetic aberrations, characterize targeted therapies used, and disease response. RESULTS: One hundred and sixty patients (median age: 7 years, range: 0–27 years) had tumor sequencing performed yielding 147 evaluable results. Low-grade lesions (LGL) (N=94, 63.9%), were mostly low-grade gliomas and glioneuronal tumors; high-grade lesions (HGL) (N=53, 36.0%) included high-grade gliomas (N=35), embryonal neoplasms (N=12), and choroid plexus carcinomas (N=3). Specific BRAF aberrations were more interrogated in LGL while larger panel sequencing was performed in HGL. Targetable aberrations were found in 99 patients (67.3%), most commonly BRAF alterations in LGL as expected, and aberrations in the RTK-PI3K pathway in HGL. Among 99 patients, 56.5% received therapy informed by sequencing data. Thirty three patients with LGL (35.1%) received targeted therapy after a median of 3 prior therapies and remained on treatment for a median of 7 months (range: 1–24 months). Twenty three patients with HGL (43.4%) received targeted therapy after a median of 2 therapies and remained on treatment for a median of 3 months (range: 1–23 months). Targeted therapy was most frequently stopped due to disease progression, only 5 patients developed toxicity that led to cessation of targeted agents. CONCLUSION: Targetable alterations are frequent in pediatric CNS tumors; when identified they guided therapy in a majority of patients commonly at progression and were used earlier and more often in HGL. GERM CELL TUMORS